2017
DOI: 10.1590/2317-6431-2017-1870
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à pressão de língua em pacientes pós-acidente vascular cerebral

Abstract: Introduction:The clinical practice of speech pathology in hospitals shows that there is a high prevalence of dysphagia in post-stroke patients. Purpose: To verify whether the time of occurrence, type of stroke, affected hemisphere, severity of neurological deficit, presence or absence of dysphagia, and degree of dysphagia interfere with tongue pressure in post-stroke patients. Methods: This study was conducted in 31 stroke patients. Three evaluations were performed, one of tongue mobility, another of dysphagia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…46,48,50, 53 The option to standardize the assessment procedures with the IOPI allows an adequate comparative analysis of findings showing maximum isometric pressure as the gold standard measure and tongue position in the anterior palate as the optimal position associated with swallowing requirements, even in studies with samples from less than 20 subjects or case studies. 46,48, 52 The use of classical protocols 54 allows researchers in the analyzed studies to provide information that can be reliably and homologously interpreted using measurements such as maximum isometric pressure, resistance and accuracy of lingual movement. This is possible despite the already observed heterogeneity of the studied neurological groups and may help future designs of therapies that include tongue strength training.…”
Section: Discussionmentioning
confidence: 99%
“…46,48,50, 53 The option to standardize the assessment procedures with the IOPI allows an adequate comparative analysis of findings showing maximum isometric pressure as the gold standard measure and tongue position in the anterior palate as the optimal position associated with swallowing requirements, even in studies with samples from less than 20 subjects or case studies. 46,48, 52 The use of classical protocols 54 allows researchers in the analyzed studies to provide information that can be reliably and homologously interpreted using measurements such as maximum isometric pressure, resistance and accuracy of lingual movement. This is possible despite the already observed heterogeneity of the studied neurological groups and may help future designs of therapies that include tongue strength training.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamori et al (2016) investigated acute stroke patients and found that patients with pneumonia had significantly lower tongue strength than those without and concluded that it is a sensitive indicator for predicting pneumonia occurrence. Oliveira et al (2017) found that stroke patients with dysphagia had lower tongue strength than those without. Beyond that, Lee and Choi (2020) claim that tongue strength has similar predictive abilities to bedside tests screening aspiration and penetration in stroke patients and even call it a new screening test to reduce the risk of pneumonia.…”
Section: Review Of Literaturementioning
confidence: 96%